Effect of Calcination Temperature on the Photocatalytic Activity of Nanostructures Synthesized by Hydrothermal Method from Black Mineral Sand (2020)
A nanostructured material from black sand, whose structure is composed by Fe2O3 and TiO2 oxides, was prepared via hydrothermal treatment (at 120 °C for 72 h), The starting mineral (as-synthesized nanostructure) was characterized by XRF spectroscopy and thermogravimetric analysis (TGA/DTA) whereas the calcined nanostructures were analyzed by scanning electron microscopy/EDX, BET single point measurements, X-ray diffraction, FTIR spectroscopy, and UV-Vis spectrophotometry. The effect of thermal treatment on structural, morphological and redox properties of nanostructured samples (NS) have been thoroughly studied in the samples calcined at 400, 700 and 1000 °C, together with a non-treated sample (M1). Their photocatalytic activity toward hydrogen production in the presence of EDTA as sacrificial agent has been tested. The as-synthetized samples calcined at 1000 °C (NS-1000) showed a higher photocatalytic activity for hydrogen production, possibly due to the transformation of magnetite into more active photocatalytical phases (hematite) driven by the changes in surface morphology (such as reduction of crystallite and pore size reduction) according to thermal equilibrium of its phases. The highest activity for photocatalytic hydrogen production was achieved by the materials calcined at 1000 °C (M1-1000 and NS-1000), while the sample calcined at lower values (<700 °C) were the least active. The catalyst activity was assigned to the appearance of a new active phase (α-Fe2O3), which improves the electronic mobility during the photocatalytic mechanism.